Effect of Organic Nitrogen Supply on the Kinetics and Quality of Anaerobic Digestion of Less Nitrogenous Substrates: Case of Anaerobic Co-Digestion (AcoD) of Cassava Effluent and Chicken Droppings as a Nitrogen Source - Haro Kayaba; Nourou Abdel Anziph Sergel Khalid; Sandwidi Sayouba; Compaore Abdoulaye; Palm Sie Auguste; Sessouma Oumou; Ouedraogo Ibrahim Kourita; Sinon Souleymane; Tubreoumya Guy Christian; Bere Antoine; Daho Tizane; Sanogo Oumar (Fuels)
This study aims to explore anaerobic co-digestion (AcoD) of cassava (EUM) and poultry (FP) effluents using one inoculum/substrate ratio (30%) and three EUM vs. FP substrate composition ratios (25:75, 50:50, and 75:25). The AcoD process was therefore designed for 20 L batch digesters, under mesophilic conditions, with less than 5% total solids for 66 days. The results showed that EUMs were highly resistant to degradation, while FPs were the most easily degradable. Kinetic analysis indicated specific organic matter (MO) reduction rates of 0.28% per day for EUM and 0.76% per day for FP. EUM alone produced 45.47 mL/g MO, while the 50:50 substrate produced 1184.60 mL/g MOV. The main factors contributing to EUM inefficiency were the inability to tame acidic conditions and the accumulation of volatile fatty acids. AcoD produced 23 to 50 times more methane than EUM alone, 2 to 5 times more than FP alone, and 2 to 4 times more than inoculum. As a result, the AcoD of both types of waste had a qualitative and quantitative effect on biogas production. CH4 content increased from around 2 to 75%, depending on the amount of organic nitrogen added. The addition of nitrogen by AcoD, even under mesophilic conditions, improves the kinetics and quality of anaerobic digestion of low-nitrogen substrates. Its impact on thermophilic and psychrophilic conditions needs to be verified.